Alcohol-related Discussions during General Medicine Appointments of Male VA Patients Who Screen Positive for At-risk Drinking - Bradley, Katharine A (Blackwell Science Inc, 2002)
OBJECTIVE: This study describes primary care discussions with patients who screened positive for at-risk drinking. In addition, discussions about alcohol use from 2 clinic firms, one with a provider-prompting intervention, are compared. DESIGN: Cross-sectional analyses of audiotaped appointments collected over 6 months. PARTICIPANTS AND SETTING: Male patients in a VA general medicine clinic were eligible if they screened positive for at-risk drinking and had a general medicine appointment with a consenting provider during the study period. Participating patients (N = 47) and providers (N = 17) were enrolled in 1 of 2 firms in the clinic (Intervention or Control) and were blinded to the study focus. INTERVENTION: Intervention providers received patient-specific results of positive alcohol-screening tests at each visit. MEASURES AND MAIN RESULTS: Of 68 visits taped, 39 (57.4%) included any mention of alcohol. Patient and provider utterances during discussions about alcohol use were coded using Motivational Interviewing Skills Codes. Providers contributed 58% of utterances during alcohol-related discussions with most coded as questions (24%), information giving (23%), or facilitation (34%). Advice, reflective listening, and supportive or affirming statements occurred infrequently (5%, 3%, and 5%, of provider utterances respectively). Providers offered alcohol-related advice during 21% of visits. Sixteen percent of patient utterances reflected “resistance” to change and 12% reflected readiness to change. On average, Intervention providers were more likely to discuss alcohol use than Control providers (82.4% vs 39.6% of visits; P = .026). CONCLUSIONS: During discussions about alcohol, general medicine providers asked questions and offered information, but usually did not give explicit alcohol-related advice. Discussions about alcohol occurred more often when providers were prompted.